Adjustment of Self-Initiated Sports Expatriates in Finland - Tossavainen, Juhani (My University, 2025)
Due to globalization and the liberating Bosman-ruling in 1995, sports expatriation has rapidly increased. Prior literature on sports expatriation classifies team sports expatriates as self-initiated expatriates (SIEs). In football, expatriates are recruited to leading roles and thus, their performance impacts on the clubs’ success significantly. Further, studies have proved that the adjustment of expatriates directly impacts their work performance. However, research on the adjustment of this subgroup of SIEs is nonexistent. Football expatriates face a peculiar work and career environment that contains pressure from unique stakeholders, highly measurable work performance, and a particular competition among team while cooperating to win as a team. In this study, self-initiated football expatriates in Finland were qualitatively studied in order to understand which factors impact their adjustment. More closely, six football expatriates were studied via semi-structured interviews discussing individual factors, general nonwork-related factors, interaction-related factors, and work-related factors affecting adjustment. The theoretical framework of this study consisted of an assigned expatriation cultural adjustment theory that was applied to fit self-initiated expatriation and sports context. The findings of this study are that football expatriates in Finland fit the key characteristics of self-initiated expatriation but contain unusual factors such as strong initiative support from the host-country organization and particularly high career orientation impacting their adjustment. Moreover, the key contribution of the study is that due to prior experience of competitive football from a young age, football expatriates in Finland adjust relatively easily to work, but poorly outside of work due to restrictive work, lack of leisure opportunities, and difficulty of interaction with the reserved locals. This indicates that clubs should invent novel ways of supporting the social adjustment of their expatriates outside of work. All in all, the adjustment experiences of sports expatriates are quite unique in comparison with other kinds of SIEs, which provides evidence for the need to study different subgroups of SIEs separately instead of treating all SIEs as one group. Globalisaation ja vuonna 1995 pelaajasiirrot vapauttaneen Bosman-säännön myötä urheiluekspatriaattien määrä on kasvanut huomattavasti. Aiempi tutkimus luokittelee joukkueurheiluekspatriaatit oma-aloitteisiksi ekspatriaateiksi (self-initiated expatriates). Jalkapallossa ulkomaiset pelaajat rekrytoidaan usein johtaviin rooleihin, jolloin heidän työsuoriutumisellansa on iso vaikutus seuran menestykseen. Tutkimus osoittaa, että ekspatriaattien sopeutumisella on suora vaikutus suoriutumiseen työssä. Silti urheiluekspatriaattien sopeutumista ei olla tutkittu. Jalkapalloekspatriaattien työ- ja uraympäristö on poikkeuksellinen muun muassa uniikkien sidosryhmien paineen, helposti mitattavan työsuoriutumisen sekä poikkeuksellisen kilpailun ja yhteistyön kombinaation takia. Tässä tutkielmassa tutkittiin kvalitatiivisesti tekijöitä, jotka vaikuttavat jalkapalloekspatriaattien sopeutumiseen Suomessa. Otoksena oli kuusi Suomeen ammattijalkapalloilijaksi muuttanutta ekspatriaattia, joiden kokemuksia kerättiin puolistrukturoiduin teemahaastatteluin. Haastatteluiden teemoina olivat henkilökohtaiset tekijät, yleiset työnulkopuoliset tekijät, kanssakäymistekijät ja työhön liittyvät tekijät. Tutkielman teoreettinen viitekehys koostui lähetettyjen ekspatriaattien (assigned expatriate) sopeutumista selittävästä teoriasta, jota sovellettiin kattamaan oma-aloitteisten ekspatriaattien ja urheilun konteksti. Tutkimustulosten perusteella Suomeen saapuneiden jalkapalloekspatriaattien piirteet kattavat oma-aloitteisen ekspatriaation keskeiset määritelmät, vaikkakin prosessissa on epätyypillisiä piirteitä kuten vastaanottavan organisaation vahva aloitteellinen tuki sekä urheilijoiden poikkeuksellisen suuri uraorientaatio. Keskeinen löydös on se, että nuoresta iästä kilpailullisesti urheilleena jalkapalloekspatriaatit sopeutuvat Suomessa työhön melko helposti, mutta työn ulkopuoliseen elämään huonosti vähäisten vapaa-ajan mahdollisuuksien, rajoittavan työn sekä paikallisten varautuneisuudesta johtuvan kanssakäymisen hankaluuden vuoksi. Tämä osoittaa, että seurojen tulisi keksiä uudenlaisia keinoja jalkapalloekspatriaattien työnulkopuolisen sosiaalisen sopeutumisen tukemiseksi. Kaiken kaikkiaan jalkapalloekspatriaattien sopeutumiskokemukset ovat melko uniikkeja verrattuna muihin oma-aloitteisten ekspatriaattien alaryhmiin. Tämä tutkielma vahvistaa aiempia näkemyksiä siitä, miten oma-aloitteisia ekspatriaatteja tulee tutkia yhden suuren kokonaisuuden sijaan erikseen alaryhminä.
Keywords: sopeutuminen; ekspatriaatit; työskentely ulkomailla; urheilu; expatriates; adjustment; sports; working abroad; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business